Association between renal function and co-infection with Clonorchis sinensis and Helicobacter pylori: a cross-sectional study - Weining Xie; Yuanjun Deng; Shengxin Chen; Yifeng Wu; Ye Li; Qinhe Yang (BMC Infectious Diseases, 2020)
Abstract Background Studies have shown that liver fluke infections may be associated with kidney injury and that Helicobacter pylori (Hp) may be involved in the pathogenesis of kidney diseases. However, no studies have reported the relationship between co-infection with Clonorchis sinensis (Cs) and Hp and renal function. The aim of this study was to examine the relationship between co-infection with Cs and Hp and estimated glomerular filtration rate (eGFR) in a general population, and gender-related differences were also investigated. Methods In the cross-sectional study, 4122 subjects from the Health Examination Center of Guangdong Provincial Hospital of Integrated Traditional Chinese and Western Medicine from January 2017 to December 2018 were enrolled. All participants underwent stool examination for the diagnosis of Cs infection and 13C-urea breath test (UBT) for the diagnosis of Hp infection. Participants were categorized into four groups: (1) co-infection with Cs and Hp group comprising 207 cases (Hp(+) + Cs(+) group), (2) Cs infection group comprising 1392 cases (Hp(−) + Cs(+)group), (3) Hp infection group comprising 275 cases (Hp(+) + Cs(−) group), and (4) non-infection group comprising 2248 cases (Hp(−) + Cs(−) group). Multiple linear regression analysis was performed to evaluate the relationship between co-infection with Cs and Hp and eGFR. Results Hp infection without Cs infection was present in 6.67% (275/4122) of subjects, while Cs infection without Hp infection was present in 33.77% (1392/4122) of subjects. Co-infection with Hp and Cs were present in 5.02% (207/4122) of subjects. Median age of the participants was 43 years (IQR 35–51). Most of the participants were male (2955/4122, 71.69%). Median eGFR was 96.61 ml/min/1.73 m2 (IQR 85.05–106.24). Co-infection with Cs and Hp was negatively associated with eGFR after full adjusting (β = − 1.89, 95% CI: − 3.33 to − 0.45, p = 0.01). The relationship remained significant in females (β = − 9.37, 95% CI: − 11.60 to − 7.1, p < 0.001), but not in males. Conclusion Our findings suggest that co-infection with Cs and Hp may be associated with reduced renal function in females, but not in males.